Best practice workplace HIV/AIDS programmes in South Africa: A review of case studies and lessons learned - Geoffrey K.G. Setswe (AOSIS, 2009)
Background: A group of experts attending a tripartite interregional meeting on best practices in HIV/AIDS workplace policies and programmes organised by the International Labour Organisation (ILO) in Geneva, Switzerland, identified 34 best practice workplace HIV programmes from across the world. Method: The ten criteria that were used for reviewing best practice workplace HIV/AIDS programmes in South Africa include acceptability, accessibility, ethical soundness, perceived impact, relevance, appropriateness, innovativeness, efficiency, sustainability and replicability. Results: More than one-third (35.3%) of the 34 best practice workplace interventions identified were found in businesses and industries in South Africa. This constitutes a significant and encouraging effort to deal with HIV/AIDS in the workplace. Approximately 16.7% of the best practice workplace HIV/AIDS interventions focused on policy and legal frameworks, 50% of these interventions focused on prevention, 16.7% provided links beyond the workplace and a further 16.7% were interventions that focused on knowledge and evidence. A third (33.3%) of practices were found in the mining industry, 16.7% in the motor industry, 16.7% from workers' unions, and the rest (33.3%) were found in a sugar company, an electricity supply company, a pharmaceutical company and the ministry of Public Service and Administration. Conclusion: It is encouraging that over one-third of all best practice workplace HIV interventions identified by the ILO experts were found in South Africa. The majority of these policies and programmes were focused on HIV prevention.